2022
DOI: 10.1186/s13058-022-01510-6
|View full text |Cite
|
Sign up to set email alerts
|

Cellular mechanisms underlying response and resistance to CDK4/6 inhibitors in the treatment of hormone receptor-positive breast cancer

Abstract: Pharmacological inhibitors of cyclin-dependent kinases 4 and 6 (CDK4/6) are now an established standard of care for patients with advanced hormone receptor-positive breast cancer. The canonical mechanism underlying CDK4/6 inhibitor activity is the suppression of phosphorylation of the retinoblastoma tumor suppressor protein, which serves to prevent cancer cell proliferation. Recent data suggest that these agents induce other diverse effects within both tumor and stromal compartments, which serve to explain asp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
39
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 73 publications
(43 citation statements)
references
References 109 publications
(201 reference statements)
4
39
0
Order By: Relevance
“…Multiple clinical trials are currently testing inhibitors of growth factor signalling pathways, such as PI3K, MEK, AKT and mTOR, together with CDK4/6 inhibitors (Fassl et al, 2022). The principle of using these combinations to achieve a sensitized G1 arrest has been extensively demonstrated in preclinical models, therefore it is logical to assume that a similar sensitized G1 arrest will also be beneficial for treating patient tumours (Alvarez-Fernandez and Malumbres, 2020; Watt and Goel, 2022). Genomic alterations that are predicted to enhance growth factor signalling pathways are also frequently associated with resistance to CDK4/6 inhibition in patients (Costa et al, 2020; Formisano et al, 2019; Wander et al, 2020), which further underscores the benefit of inhibiting these pathways in combination to effectively block G1 progression.…”
Section: Discussionmentioning
confidence: 99%
“…Multiple clinical trials are currently testing inhibitors of growth factor signalling pathways, such as PI3K, MEK, AKT and mTOR, together with CDK4/6 inhibitors (Fassl et al, 2022). The principle of using these combinations to achieve a sensitized G1 arrest has been extensively demonstrated in preclinical models, therefore it is logical to assume that a similar sensitized G1 arrest will also be beneficial for treating patient tumours (Alvarez-Fernandez and Malumbres, 2020; Watt and Goel, 2022). Genomic alterations that are predicted to enhance growth factor signalling pathways are also frequently associated with resistance to CDK4/6 inhibition in patients (Costa et al, 2020; Formisano et al, 2019; Wander et al, 2020), which further underscores the benefit of inhibiting these pathways in combination to effectively block G1 progression.…”
Section: Discussionmentioning
confidence: 99%
“…In order to address this issue, several genomic and retrospective analyses have been performed, and many others are still ongoing. In particular, research efforts are focusing on circulating biomarkers, given their many advantages in terms of ease of application and reproducibility at different time points that can capture spatial and temporal heterogeneity [ 41 , 42 ]. Retrospective analyses of large, randomized trials, PALOMA-2 and 3 and MONALEESA, have suggested a correlation between intrinsic subtype and efficacy of palbociclib and ribociclib in HR+/HER2- ABC treated with endocrine-based strategies.…”
Section: Discussionmentioning
confidence: 99%
“…Since our ultimate goal is to delay or prevent the onset of drug resistance, adding resistance mechanisms to the model is a critical requirement for future work (Wander et al, 2020; Asghar et al, 2022; Pandey et al, 2022, Papadimitriou et al, 2022). The cyclinD1 change mentioned above is a minor step in that direction, but the development of resistance is a complex, multi-faceted process and there are many different pathways that lead to a drug resistant state (Lloyd et al, 2022; Watt et al, 2022). To see whether a therapeutic protocol delays the emergence of resistance compared to monotreatment will require experiments over time periods of many months, necessitating the use of mathematical models to propose the most promising protocols to explore (Serra etl al., 2019; Waller et al, 2019; Llombart-Cussac et al, 2021).…”
Section: Discussionmentioning
confidence: 99%